2022
DOI: 10.3390/land11050592
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Change in Urban Green Infrastructure—Evidence from Romania and Poland

Abstract: The extent and continuity of green infrastructure can be adjusted by planning. Depending on the sense of the adjustment, the process can lead to a vicious cycle, resulting in poorer urban quality, or to a virtuous planning, thus leading to psychological wellbeing and sustainability. However, socioeconomic circumstances also play an important role in managing green infrastructure. Starting from these premises, the current study aims to take an in-depth look at the mechanisms of change in urban green infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…At the same time, planners are responsible for limiting exposure by not permitting the development and movement of population into the hotspots prone to hazards that have been identified in this study. In general, our study provides additional arguments as to why planners should be more sensitive to scientific evidence, especially that which advocates for green infrastructure, which should be embedded in the spatial planning and translated into specific restrictions (Petrişor et al, 2022).…”
Section: Ta B L Ementioning
confidence: 87%
“…At the same time, planners are responsible for limiting exposure by not permitting the development and movement of population into the hotspots prone to hazards that have been identified in this study. In general, our study provides additional arguments as to why planners should be more sensitive to scientific evidence, especially that which advocates for green infrastructure, which should be embedded in the spatial planning and translated into specific restrictions (Petrişor et al, 2022).…”
Section: Ta B L Ementioning
confidence: 87%
“…The green-blue infrastructure of Bucharest and its dynamic were investigated by Petrişor et al [14,41], based on Urban Atlas data. According to the aforementioned studies, the green-blue infrastructure of Bucharest consists mainly of agricultural areas (64%), followed by green spaces (20%), forests and natural areas (11%), and leisure areas (5%) [41]. As can be seen, landscaped areas make up one fourth of the green infrastructure.…”
Section: Green-blue Infrastructure In Romaniamentioning
confidence: 99%
“…Previous studies conducted in the Romanian context have highlighted the adverse consequences of this form of development [43]. Dense sprawl has resulted in traffic issues [44], the depletion of green infrastructure [45], and the emergence of new residential areas with substandard housing conditions [30]. By examining Bucharest as a case study using satellite imagery and field studies, two types of new residential developments were observed:…”
Section: Development Of New Residential Areasmentioning
confidence: 99%